Morphological study and lignin degradation of pathogenic ganoderma species of basal stem rot in oil palm - Wong, Ling Chie (2013)
Basal stem rot (BSR) is one of the most serious diseases causing major losses in the oil palm industry in Southeast Asia, especially in Malaysia and Indonesia. Several species of Ganoderma have been reported to be pathogenic to oil palm, however, the diversity and differentiation of the Ganoderma species were not widely studied and the identity of these species are still unclear leading to inaccurate and inefficient decision-making in disease management. In this study, several isolates of Ganoderma were collected in Sarawak, Malaysia and Multiplex Polymerase Chain Reaction was carried out to differentiate the isolates into species level. This was followed by macromorphological, micromorphological and compatibility studies of the Ganoderma isolates. Lignin degradation study on the isolates was also carried out. Multiplex PCR-DNA analysis demonstrated positive results for G. boninense, G. zonatum and G. miniatocinctum, indicating that these three Ganoderma species were associated with the basal stem rot disease in Sarawak. Compatibility study had shown that isolates from different palms were not compatible. Morphological studies of the Ganoderma isolates showed that hyphae characteristics and spore length can be used to distinguish among the Ganoderma species. Therefore an identification key was developed as a guideline on species differentiation of the pathogenic Ganoderma species. Isolates of G. zonatum G46 and G. miniatocinctum G30, demonstrated similar lignin degrading ability as G. boninense G25 and G47 whereby G. zonatum G46 was capable of degrading the most amount of lignin after a week of infection. From week 1 to week 5, G. zonatum G46 was able to degrade more lignin compared to G. boninense G25 and G47, indicating that G. zonatum could cause more damage to oil palms for long term. Therefore, more researches should emphasize on G. zonatum instead of focusing on G. boninense alone in order to formulate suitable solutions to control or eliminate BSR caused by the different Ganoderma species.